STUDI PERBANDINGAN KONSEP NEGARA YANG IDEAL MENURUT IBNU RUSYD DAN AL-FARABI - Saipul Nasution; Fazari Zul Hasmi Kanggas; Yaumi Sa'adah; Muhammad Azrul Amirullah (Universitas Ibn Khaldun Bogor, 2026)
In this article, we as authors would like to discuss a comparative study of the concept of an ideal state according to Ibn Rushd and Al-Farabi, both of whom were Muslim scholars who lived in the Middle Ages, a period when Islam flourished with knowledge ranging from politics, law, philosophy, medicine, architecture, and so on. The purpose of this study is to identify the differences in their formulations regarding how a state can become the best possible framework, whose implementation has a significant impact on the lives of its people. The research method employed in this study is library research. In his previous explanation, Ibn Rushd emphasised three concepts, namely the ideal state, which is the sovereignty of the people (al-siyadah), freedom (al-hurriyah), equality (al-musawah), and diversity (pluralism). These concepts form the basis for a just and prosperous state according to his thinking. Meanwhile, Al-Farabi's concept of the ideal state, called al-Madinah al-Fadhilah, is a state that aims to achieve worldly and eternal happiness for all its citizens. This state is led by a wise philosopher-king who has extensive knowledge and is able to lead society towards moral and spiritual perfection. By introducing the concept of Philosopher-Prophet Leadership (scholars), Happiness, Structured Society, Justice and Prosperity, a Just Economic System, Education and Morality.